Renal allograft dysfunction: An update on immunological graft injury - Praveen Kumar Etta; M V Rao (Indian Journal of Transplantation, 2019)
Renal transplantation is the treatment of choice in most patients with end-stage renal disease, especially with improvement in surgical techniques and immunosuppressive regimens; however, the long-term graft survival remains to be improved. Immunological graft injury leading to rejection plays a major role in long-term graft loss. With pretransplant immunological evaluation using various crossmatch tests, identification of donor-specific antibodies, a better understanding of renal allograft pathology and its standardization with the Banff classification having regular updates led to prevention, early and accurate diagnosis of rejection and its histological differentiation. Some newer biomarkers are in pipeline may enable early and accurate identification of graft pathology noninvasively.